Between sustainability commitments and anticipated market requirements: Exploring the resilience of the techno-economic innovation paradigm in the midstream of construction research - Frost, Deniz; Braun, Kathrin; Kropp, Cordula (NOvation — Critical Studies of Innovation, 2022)
This article studies ways of dealing with the tension between a commitment to sustainable and responsible research and anticipated market requirements in the midstream of a research process in architecture and construction. Using a slightly modified version of Socio-Technical Integration Research (STIR), we explored the chances of questioning the primacy of the techno-economic innovation paradigm by deliberately provoking reflections through STIR interactions. Our research underlines the difficulties and limitations of challenging an orientation towards values of efficiency and productivity in favour of social and environmental values in the midstream of the research process and examines how the techno-economic innovation paradigm is able to insulate itself against critical questioning. It sheds light at the critical role of the underlying assumption that marketability of prospective outcomes is not one objective amongst others but the precondition for all others and at two argumentative patterns we termed the "lack-of-agency" and the "reconciliation-after-all" pattern.